Characteristics and Motivation of the Millennial Generation to Take Gastronomic Tourism Travels - Sri Puspa Dewi, Roels Ni Made; Utami, Nisa Rahmaniyah (Stupa, 2024)
The millennial generation's travel patterns are starting to like gastronomic tourism. Djejak Rasa Yogyakarta is here as a forum for the millennial generation as well as media while getting to know more about the gastronomy contained in the culinary offerings. The purpose of this study is to get an overview of the characteristics and motivations for choosing Djejak Rasa for gastronomy tours. The research method uses distributing questionnaires on the Google form which can be filled out by tourists after a tour of 50 people. Data analysis was carried out interactively models. The results of this study are the characteristics of millennial generation tourists in conducting gastronomic trips as a tourist descriptor and the trip descriptor. The motivation for tourists to take a gastronomic journey with Djejak Rasa are physical motivation, cultural motivation, individual motivation and status motivation.